Correlation between Neutrophil-to-Lymphocyte Ratio (NLR) and Immature-to-total Neutrophil (I/T) Ratio to Bacterial Infection among Children with Chronic Kidney Disease - Galuhafiar Puratmaja; Anggraini Alam; Dzulfikar Djalil Lukmanul Hakim; Sri Endah Rahayuningsih; Dida Akhmad Gurnida; Dany Hilmanto (Althea Medical Journal, 2022)
Background: Chronic kidney disease (CKD) in children has a long-lived impact, such as an increased risk of bacterial infection. Infection may accelerate disease progression, making early detection crucial. Inflammatory markers typically used for bacterial infection are C-Reactive Protein (CRP) and Procalcitonin (PCT). This study aimed to determine the correlation between levels of neutrophil-to-lymphocyte ratio (NLR) and immature-to-total-neutrophil ratio (I/T ratio) to bacterial infection in children with CKD as indicated by the serum levels of CRP and PCT.